Direct and correlated responses to selection for longevity in Drosophila buzzatii - Scannapieco, A.C. (2009)
The possible associations between longevity, early fecundity, and stress-resistance traits were explored using artificial selection on longevity in a laboratory population of Drosophila buzzatii. Three replicated lines were selected for increased lifespan (L lines) and compared with the respective unselected controls (C lines) after the 14th generation of selection. Mean longevity exhibited a significant response to selection. The baseline mortality tended to decrease in the L lines and a negative correlated response to longevity selection was found for early fecundity. Egg-to-adult developmental time increased in L lines. Longevity selection increased stress resistance for both high and low temperatures, as measured by heat knockdown resistance and chill-coma recovery. Starvation resistance also tended to be higher in L than in C lines. The results obtained are consistent with the hypothesis of trade-offs between longevity and early fecundity, and also suggest a trade-off association between adult longevity and developmental time. Correlated selection responses were generally consistent with correlations among the traits previously inferred from altitudinal clines for longevity and stress-resistance phenotypes. © 2009 The Linnean Society of London.